Optimization of School Administration with Augmented Reality and Payment Gateway - Tju, Teja Endra Eng; Sidik, Fajar (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
The rapid advancement of digital technology has highlighted the need for efficient and transparent school administration systems. Traditional manual student profile management and tuition payment processes often lead to delays, errors, and inefficiencies. This study proposes an integrated system that combines Augmented Reality (AR) for student profile photo standardization and a Payment Gateway for automated financial transactions. The AR feature enables students to capture standardized profile photos directly through the application, ensuring compliance with school regulations while reducing administrative workload. Simultaneously, the Payment Gateway supports multiple digital payment methods, enhancing transaction speed, security, and transparency. The research follows a four-stage methodology: Needs Analysis, Prototype Design, Application Development, and Testing & Refinement. Through Needs Analysis, key administrative challenges were identified, guiding the design and development of the system. The prototype was developed using Laravel for the backend, React for the front end, OpenCV for AR processing, and Midtrans as the Payment Gateway provider. Extensive testing, including User Acceptance Testing, demonstrated the system’s effectiveness in streamlining administrative tasks. The AR-based profile photo verification and secure online payment processing significantly improved user experience and efficiency. Refinements were made to optimize system performance, including enhanced image processing for low-quality cameras, real-time transaction retry mechanisms, and User Interface improvements for better navigation. This study contributes to the digital transformation of school administration by integrating AR and Payment Gateway technologies, providing a scalable, efficient, and user-friendly solution for educational institutions.